Detection of antibiotic resistant pigmented bacteria in raw water, finished drinking water and tap water from Muntinlupa City - Talosig, Janet Q.
The presence of antibiotic resistant bacteria in drinking water is an emerging health issue. While only a few of the antibiotic resistant bacteria are opportunistic pathogens, all of them can serve as reservoir of resistance genes that can be transferred to organisms that often cause clinical diseases making the treatment difficult. However, the detection of these organisms is not included in the 2007 Philippine National Standards for Drinking Water. The present study is a descriptive study that determined the occurrence of antibiotic resistance in pigmented bacteria found in raw water, finished drinking water and tap water from Muntinlupa City. Pigmented bacteria were selected because of their abundance in chlorinated water and because they are more resistant than the non-pigmented bacteria. Lot Quality Assurance Sampling (LQAS) was used in the determination of tap water sample size. Sample sizes of raw water and finished drinking water were based on previous studies done outside the country. R2A agar incubated with the water sample at 35 degrees Celsius for 5 days was used to enumerate the heterotrophic plate count (HPC). The HPC of the water samples were found to be 2.7x105 cfu/mL, 3.8 cfu/mL for raw water, finished drinking water and tap water, respectively. The percentage of pigmented bacteria was higher in tap water as compared with raw water. Pigmented bacteria was absent from finished drinking water. Disk diffusion susceptibility test was done to screen the resistance of the pigmented isolates against ampicillin, cefotaxime, chloramphenicol, gentamicin, tetracycline and sulfamethoxazole trimethoprim. Among the 15 pigmented bacteria isolated from raw water, 5 (33.3%) were resistant. These included one Psudomonas otitidis, one Deinococcus grandis, two Aeromonas spp., and one unidentified non-fermenter. Among the tap water pigmented bacterial isolates 20 out of 48 (41.7%0 were resistant. These were composed of seven non-tuberculous Mycobacteriumspp., three Pseudomonas aeruginosa, three Pseudomonas alcaligeneses, two Sphigomonas natatoria/ursincola, one Stenotrophomonas matophilia, once Cupriavidus spp., and three unidentified non-fermenter. Since five out of the six tap water samples contained antibiotic resistant pigmented bacteria, it is highly suggested that the prevalence of antibiotic resistant pigmented bacteria in tap water from Muntinlupa City is at least 60%
Thesis (MS Public Health, Medical Microbiology)--University of the Philippines Manila.
Keywords: Water; Drug resistance in microorganisms